The Impact of the Closing of the Tanjung Batu Merah Localization Place on Community Income in RT 002/ RW 010 Sirimau District, Ambon City - Salim Marasabessy; William Louhenapessy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to analyze the impact of the closure of the Tanjung Batu Merah localization site, Ambon City, on the income of community retail traders around the Tanjung Batu Merah Localization. The sample in this study were 32 retail traders. The data collection technique in this study was a questionnaire. The analysis technique used in this study was t-test analysis. The t-test used was a pair sample t-test. Normality, Homogeneity test, Linearity test. The results showed that there was a significant difference in the profit of retail traders, before and after the closing of the localization place, the decrease in the average profit of retail traders before and after the closing of the localization place was seen from the average profit of the traders before the closing of the localization place of Rp. 1,326. 562, - decreased to Rp. 568,750, - after the localization place was closed, as well as the income of retail traders, seen from the average income of traders before the localization place was closed, amounting to Rp. 2,627,812, - decreased to Rp. 1,102,625, - after the localization place was closed. Meanwhile, the sign value of the t-test obtained was 0.000 0.05 indicating a significant impact on the income and profits of retail traders in the Tanjung community, Batu Merah Village.